Comparison of bile salt/phosphatidylcholine mixed micelles in solubilization to sterols and stability - Guo Q; Cai J; Li PY; Xu DL; Ni XM; Wen H; Liu D; Lin SZ; Hu HY (Dove Medical Press, 2016)
Qin Guo,1,* Jie Cai,1,2,* Pengyu Li,1 Dongling Xu,1 Xiaomin Ni,1 Hui Wen,3 Dan Liu,3 Suizhen Lin,3 Haiyan Hu1 1School of Pharmaceutical Sciences, Sun Yat-sen University, 2Guangzhou First People’s Hospital, Guangzhou Medical University, 3Guangzhou Cellprotek Pharmaceutical Co., Ltd., Science Park, Guangzhou, People’s Republic of China *These authors contributed equally to this work Abstract: Androst-3β,5α,6β-triol (Triol) is a promising neuroprotective agent, but its poor solubility restricts its development into parenteral preparations. In this study, Triol is significantly solubilized by bile salt/phosphatidylcholine mixed micelles (BS/PC-MM). All BS/PC-MM systems are tested to remarkably improve the drug solubility with various stabilities after drug loading. Among them, the sodium glycocholate (SGC)/egg phosphatidylcholine (EPC) system with 2:1 ratio in weight and the total concentration of SGC and EPC of 100 mg/mL is proved to produce stable mixed micelles with high drug loading. It is found that the stability of drug-loaded mixed micelles is quite different, which might be related to the change in critical micelle concentration (CMC) after incorporating drugs. SGC/EPC and SGC/soya phosphatidylcholine (SPC) remain transparent under accelerated conditions and manifest a decreased CMC (dropping from 0.105 to 0.056 mg/mL and from 0.067 to 0.024 mg/mL, respectively). In contrast, swine bile acid-sodium salt (SBA-Na)/PC and sodium deoxycholate (SDC)/PC are accompanied by drug precipitation and reached the maximum CMC on the first and the third days, respectively. Interestingly, the variation of CMC under accelerated testing conditions highly matches the drug-precipitating event in the primary stability experiment. In brief, the bile salt/phosphatidylcholine system exists as a potential strategy of improving sterol drug solubility. CMC variation under accelerated testing conditions might be a simple and easy method to predict the stability of drug-loaded mixed micelles. Keywords: bile salt/phosphatidylcholine, mixed micelles, sterols, solubilizing, stability